Non-motor symptoms and quality of life in dopa-responsive dystonia patients. (December 2017) - Timmers, E.R.; Kuiper, A.; Smit, M.; Bartels, A.L.; Kamphuis, D.J.; Wolf, N.I.; Poll-The, B.T.; Wassenberg, T.; Peeters, E.A.J.; de Koning, T.J.; Tijssen, M.A.J.
Abstract: Background: In patients with GTP-cyclohydrolase deficient dopa-responsive dystonia (DRD) the occurrence of associated non-motor symptoms (NMS) is to be expected. Earlier studies report conflicting results with regard to the nature and severity of NMS. The aim of our study was to investigate the prevalence of psychiatric disorders, sleep problems, fatigue and health-related quality of life (HR-QoL) in a Dutch DRD cohort. Methods: Clinical characteristics, motor symptoms, type and severity of psychiatric co-morbidity, sleep problems, fatigue and HR-QoL were assessed in DRD patients with a confirmed GCH1 mutation and matched controls. Results: Twenty-eight patients were included (18 adults and 10 children), from 10 families. Dystonia symptoms were well-controlled in all patients. According to the DSM IV patients significantly more often met the criteria for a lifetime psychiatric disorder than controls (61% vs. 29%, p < 0.05). In particular the frequencies of generalized anxiety and agoraphobia were higher in patients (both 29% vs. 4%, p < 0.05). Patients scored significantly higher on daytime sleepiness than controls (ESS, 11.2 vs 5.7, p < 0.05). Adult patients had significantly lower scores on the mental component of the HR-QoL (47 vs. 54, p < 0.05) than controls mainly associated with (worse) quality of sleep. Conclusion: NMS were highly prevalent in our cohort of DRD patients, despite adequate treatment of motor symptoms. Our findings support the accumulating evidence of an important non-motor phenotype in DRD, with possible involvement of serotonergic mechanisms. This highlights the need to address NMS and the underlying neurobiology in patients with DRD. Highlights: Generalized anxiety and agoraphobia are highly prevalent in DRD patients. Psychiatric disorders in DRD are not related to motor symptoms. Excessive daytime sleepiness is highly prevalent in DRD patients. DRD patients scored lower on the mental component of the HR-QoL than controls. HR-QoL in DRD patients is associated with sleep problems and fatigue.